Changes in risk behaviors among Thai men who have sex with men and transgender women enrolled in the test and treat cohort. Issue 9 (2nd September 2019) - Hiransuthikul, Akarin; Trachunthong, Deondara; Pattanachaiwit, Supanit; Teeratakulpisarn, Nipat; Chamnan, Parinya; Pathipvanich, Panita; Thongpaen, Suchart; Pengnonyang, Supabhorn; Nonenoy, Siriporn; Lertpiriyasuwat, Cheewanan; Phanuphak, Praphan; Phanuphak, Nittaya
ABSTRACT: The test-and-treat approach has the potential to reduce high-risk sexual behaviors by linking high-risk individuals to health education, although this has not been proven yet. We used longitudinal data from the Test and Treat Demonstration Project among Thai men who have sex with men (MSM) and transgender women (TGW) who were not known to be HIV-positive to analyze changes in risk behaviors during the 24-month study period categorized by three groups: HIV-negative without seroconversion, seroconverters, and HIV-positive at enrollment. Five binary risk behavior outcomes – laboratory-diagnosed sexually transmitted infections (STIs); multiple sexual partners, unprotected anal intercourse, self-perceived HIV risk, and amphetamine-type stimulants use in the past month – were assessed. Among 689 participants, with a mean (SD) age of 23.1 (6.2) years, 165 participants were diagnosed with HIV: 115 at enrollment and 50 with seroconversions. HIV-positive participants at enrollment showed significant reductions in all five behavioral risk outcomes. Seroconverters demonstrated higher risks at enrollment than HIV-negative participants, and continued to practice high-risk behaviors even after seroconversion despite a significant reduction in self-perceived moderate-to-high HIV risk. Continuation of risk behaviors among seroconverters could negatively affect the ending AIDS goal, thus the integration of other effective preventive measures into HIV/STIs management programs are needed.